(untitled) (Psychology Travelogs, 2025)
The article presents the results of a study aimed at identifying the peculiarities of psychological defences and coping strategies in teachers with different levels of psychological well-being. Based on the data obtained and on the works of other authors, it can be noted that the prevalence of coping strategies aimed at solving a difficult situation or avoidance can be an important factor in the psychological well-being of teachers. The study has led to the conclusion that teachers with different levels of psychological well-being may differ in psychological defences and coping strategies. The obtained results showed that teachers with a high level of psychological well-being are more likely to use adaptive psychological defences, teachers with an average level of psychological well-being are more likely to use infantile type psychological defences, teachers with a low level of psychological well-being are more likely to use psychotic, as well as infantile and neurotic types of psychological defences. Teachers with a high level of psychological well-being are distinguished by a preference for coping strategies belonging to the type of ‘Orientation towards rapprochement, interaction with difficulties’. Teachers with medium and especially low levels of psychological well-being tend to use coping strategies of the type ‘Orientation towards avoidance and distance from difficulties’ more often. It is recommended to use the results of the study in psychoprophylactic and psychocorrectional work with teachers. The results of the study will be useful for teachers, psychologists and specialists who interact with teachers. The results of the study can be used in psychoprophylactic and psychocorrectional work with teachers.